Genomics of Serratia marcescens Isolates Causing Outbreaks in the Same Pediatric Unit 47 Years Apart: Position in an Updated Phylogeny of the Species - Saralegui, Claudia; Ponce Alonso, Manuel; Pérez Viso, B; Moles Alegre, L; Escribano, E; Lázaro Perona, F; Lanza, Val F.; de Pipaón, MS; Rodríguez, JM; Baquero, F; del Campo Moreno, Rosa (My University, 2020)
The first documented nosocomial outbreak caused by Serratia marcescens in Spain occurred in 1969 at the neonatal intensive care unit (NICU) of the tertiary La Paz Children¿s Hospital in Madrid, Spain, and based on the available phenotyping techniques at this time, it was considered as a monoclonal outbreak. Only 47 years later, another S. marcescens outbreak of an equivalent dimension occurred at the same NICU. The aim of the present study was to study isolates from these historical and contemporary outbreaks by phenotypic analysis and whole-genome sequencing techniques and to position these strains along with 444 publicly available S. marcescens genomes, separately comparing core genome and accessory genome contents. Clades inferred by both approaches showed high correlation, indicating that core and accessory genomes seem to evolve in the same manner for S. marcescens. Nine S. marcescens clusters were identified, and isolates were grouped in two of them according to sampling year. One exception was isolate 13F-69, the most genetically distant strain, located in a different cluster. Categorical functions in the annotated accessory genes of both collections were preserved among all isolates. No significant differences in frequency of insertion sequences in historical (0.18¿0.20)¿excluding the outlier strain¿versus contemporary isolates (0.11¿0.19) were found despite the expected resting effect. The most dissimilar isolate, 13F-69, contains a highly preserved plasmid previously described in Bordetella bronchiseptica. This strain exhibited a few antibiotic resistance genes not resulting in a resistant phenotype, suggesting the value of gene down expression in adaptation to long-term starvation. Keywords: Serratia marcescens, phylogeny, resistome, antibiotic susceptibility, nosocomial outbreak